Kan du tage pigen op af kufferten? En analyse af sproglig evaluering i daginstitutioner - Lars Holm (Educare)
The article presents results from a study in language testing of children in two kindergartens in Copenhagen. Closely related to poor PISA-results in reading in the Danish schools language testing in Danish kindergartens have been vastly extended. This has caused an intense and heated debate among scholars, in which the extended language testing in Kindergartens are supported or opposed, based on either generalized perspectives on expected school progress or on generalized perspectives on the harm testing practices might do children in kindergartens. The study reported in this article goes beyond these generalized perspectives from “the outside”, and points to the necessity of an ethnographic-oriented “insideperspective” in which kindergartens language testing is researched empirically as a local and social practice. A theoretical framework for researching language testing as a social practice is developed and applied to ethnographic date from fieldwork in two kindergartens in Copenhagen. The study shows that the view of language and the view of measurement and knowledge embedded in the language test results in specific institutional practices in which the interaction between the child and the preschool-teacher focusses on children’s receptive knowledge of structural components of language. Furthermore the practices appear to be based on highly normative assumptions about children´s language development and everyday life. The analysis shows that the social practices around language testing are placing children in a position in which their potential as creative and productive producers of language in interaction is absent from the agenda. The implications of this for the ongoing development of kindergarten practices and for pre-school teachers are discussed.